2000
DOI: 10.1037/0022-006x.68.6.957
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a cognitive–behavioral treatment for generalized anxiety disorder: Evaluation in a controlled clinical trial.

Abstract: Recent advances in the understanding of worry have led to the development of treatments for generalized anxiety disorder (GAD). The present study tested a GAD treatment that targeted intolerance of uncertainty, erroneous beliefs about worry, poor problem orientation, and cognitive avoidance. Twenty-six primary GAD patients were randomly allocated to a treatment condition (n = 14) or a delayed treatment control condition (n = 12). Self-report, clinician, and significant other ratings assessed GAD and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
217
2
21

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(252 citation statements)
references
References 35 publications
12
217
2
21
Order By: Relevance
“…A number of studies showed superiority of CBT to a waiting list group (Barlow et al 1992;Butler et al 1991;Dugas et al 2003;Ladouceur et al 2000;Lindsay et al 1987;Mohlman et al 2003). Moreover, comparisons with a ''psychological placebo'', a pill placebo or comparable control group conditions showed that CBT has not only unspecific psychotherapy effects, but also specific ingredients (Borkovec et al 1987;Borkovec and Costello 1993;Linden et al 2005;Power et al 1990;Stanley et al 2003).…”
Section: )(D)mentioning
confidence: 99%
“…A number of studies showed superiority of CBT to a waiting list group (Barlow et al 1992;Butler et al 1991;Dugas et al 2003;Ladouceur et al 2000;Lindsay et al 1987;Mohlman et al 2003). Moreover, comparisons with a ''psychological placebo'', a pill placebo or comparable control group conditions showed that CBT has not only unspecific psychotherapy effects, but also specific ingredients (Borkovec et al 1987;Borkovec and Costello 1993;Linden et al 2005;Power et al 1990;Stanley et al 2003).…”
Section: )(D)mentioning
confidence: 99%
“…However, it is impossible to avoid uncertainty or ambiguity in life, which means that individuals who are severely intolerant of uncertainty would be constantly faced with situations that they experience as anxiety provoking. Intolerance of uncertainty has been viewed as a central process in conceptualizations of pathological worrying and is also an important target for clinical intervention in the treatment of Generalized Anxiety Disorder Ladouceur et al, 2000), characterized by excessive and uncontrollable worry and anxiety (American Psychiatric Association, 1994).…”
Section: Intolerance Of Uncertaintymentioning
confidence: 99%
“…Since 1990, the PSWQ has been widely used as a self-report measure of worry and GAD. The PSWQ has also been used in most treatment outcome studies of GAD Borkovec and Costello, 1993;Ladouceur et al, 2000), laboratory investigations (Butler et al, 1995), and GAD psychopathology studies (Beck et al, 1996).…”
Section: Introductionmentioning
confidence: 99%